Sex Hormones and Gender Influence the Expression of Markers of Regulatory T Cells in SLE Patients - Singh, Ram P.; Bischoff, David S. (Frontiers in Immunology, 2021)
Regulatory T cells have been implicated in the regulation and maintenance of immune homeostasis. Whether gender and sex hormones differentially influence the expression and function of regulatory T cell phenotype and their influence on FoxP3 expression remains obscure. We provide evidence in this study that the number and percent of human regulatory T cells (Tregs) expressing CD4+ and CD8+ are significantly reduced in healthy females compared to healthy males. In addition, both CD4+CD25+hi and CD8+CD25+hi subsets in healthy males have a 2-3 fold increase in FoxP3 mRNA expression compared to healthy females. Female SLE patients, compared to healthy women, have elevated plasma levels of estradiol and decreased levels of testosterone. Higher levels of testosterone correlate with higher expression of FoxP3 in CD4+CD25hiCD127low putative Tregs in women with SLE. Incubation of CD4+ regulatory T cells with 17-estradiol at physiological levels generally decreased FoxP3 expression in females with SLE. These data suggest that females may be more susceptible than males to SLE and other autoimmune diseases in part because they have fewer Tregs and reduced FoxP3 expression within those cells due to normal E2 levels which suppress FoxP3 expression. In addition, low levels of plasma testosterone in women may further reduce the ability of the Tregs to express FoxP3. These data suggest that gender and sex hormones can influence susceptibility to SLE via effects on regulatory T cells and FoxP3 expression.